Bone healing in critical-size defects treated with either bone graft, membrane, or a combination of both materials: a histological and histometric study in rat tibiae - Bernabé, Pedro Felício Estrada [UNESP]; Nascimento Melo, Luiz Gustavo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP]; Dezan Junior, Eloi [UNESP]; Nagata, Maria José Hitomi [UNESP] (Wiley-Blackwell, 2012)
Objectives: The aim of the present investigation was to histologically analyze the effect of using lyophilized bovine bone (GenOx (R) organic matrix) with (or without) guided tissue regeneration (using a decalcified cortical osseous membrane [GenDerm (R)]) on bone healing in surgically created critical-size defects created in rat tibia.Material and methods: Surgical critical-size bone defects were created in 64 animals that were randomly divided into four groups: group I (control); group II (defect filled with GenOx (R)); group III (defect covered by GenDerm (R)); group IV (defect filled with GenOx (R) and covered by GenDerm (R)). Animals were killed at 30 or 90 days post-surgery. The specimens were embedded in paraffin, serially cut, and stained with hematoxylin and eosin for analysis under light microscopy. The formation of new bone in the cortical area of the defect was histomorphometrically evaluated.Results: All experimental groups demonstrated superior bone healing compared with the control group. However, group IV samples showed evidence of more advanced healing at both 30 and 90 days post-surgery as compared with the other experimental groups.Conclusions: The bovine organic bone graft GenOx (R) associated with GenDerm (R) this produced the best treatment results in the case of critical-size defects in rat tibia.
Keywords: bone regeneration; bone substitutes; guided tissue regeneration